Characterisation of Sweet potato collusive virus (SPCV) isolates from sweet potato (Ipomea batatas) in Australia - Amit C. Sukal; Sandra Dennien; Dawit B. Kidanemariam; Karlah Norkunas; Eric Coleman; Robert M. Harding; Anthony P. James (Australasian Plant Pathology, 2022)
Sweet potato collusive virus (SPCV) is a member of the genus Cavemovirus , family Caulimoviridae , for which only one full-length genome sequence has been reported. SPCV was first detected in Australia in 2007 in two sweet potato accessions using the nitrocellulose membrane ELISA kit developed by the International Potato Centre (CIP). Infected plants were also shown to contain isometric virions of ~ 50 nm, typical of members of the genera Cavemovirus , Caulimovirus , Petuvirus and Soymovirus . We have now sequenced and characterised the complete genomes of the two SPCV isolates (designated SPCV-Aus1 and -Aus2) using a combination of next-generation sequencing and PCR/Sanger sequencing. The sequences of both isolates encode three major ORFs with a genome organisation typical of cavemoviruses. However, isolate SPCV-Aus2 possesses a considerably shorter genome length of 7275 bp compared to SPCV-Aus1 (7712 bp) and the only available full-length sequence from a Portuguese isolate (7723 bp; GenBank accession number NC_015328). Further, ORF 1 of SPCV-Aus2 is considerably shorter than the ORF 1 length of both SPCV-Aus1 and SPCV-Mad1. Phylogenetic and PASC analysis showed that SPCV-Aus1 is closely related to SPCV isolates from North and Central America, whereas SPCV-Aus2 clustered together with isolates from Portugal and Africa.